Analisis Pendapatan dan Keberlanjutan Usahatani Jeruk Nipis di Desa Watabenua Kecamatan Landono Kabupaten Konawe Selatan - A, Arneni; Salam, Idrus; Yusria, Wa Ode (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Lime plants (citrus aurantifolia) are one type of Citrus Gerut. With the existence of profitable agricultural products, this Lime fruit becomes income for the community. The reality that occurs among farmers is that farmers rarely even have to calculate in detail the economic analysis of farming. The existence of a clear farming analysis means that farmers will be able to know exactly how much their farming costs will be, the size of the income earned by farmers greatly affects the motivation of farmers themselves in doing farming. Sustainability of farming in the economic aspect is seen from the level of income of Lime farmers. This study aims to determine the income and sustainability of lime farming in Watabenua Village, Landono District, South Konawe Regency. This research was carried out in Watabenua Village, Landono District, South Konawe Regency from June 2021 to completion. The sample in this study amounted to 33 people who were determined using the census technique. The data used are primary and secondary. The method used in this research is descriptive and analytical. The results showed that the average income of lime farmers in Watabenua Village, Landono District, South Konawe Regency was Rp. 22,586,265. The average monthly income of farmers is Rp.1,882,188, from Rp.22,680,368/year with a production cost of Rp.4,637,977/year. Lime farming in Watabenua Village, Landono District, South Konawe Regency, if determined from the economic aspect, is sustainable.